HUBUNGAN KETIDAKINGINAN MENAMBAH ANAK DENGAN PERILAKU KB PADA PASANGAN MUDA DI INDONESIA: Analisis SDKI 2012 - , HERI KUSYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In Indonesia, the achievement of Contraceptive Prevalence Rate (CPR) increased, but not accompanied by a decrease in Total Fertility Rate (TFR). The desire to add the next child after second child at a young couple possible contributor TFR. Desire to add the next child after has two children at the young couple be a possible contributor to the rising TFR. Starting from the problems of research activities carried out to examine the relationship unwillingness to add a child to the behavior of family planning in Indonesia. The method was used a survey research with cross sectional design using IDHS 2012 data research subject monogamous married couples, wives aged 15-35 years and had two children. Chi-square statistical test and logistic regression with Confidence Interval (CI) of 95% and p <0.05. Of the 1,380 young couple found 48.3% wanted more children, only 22.4% who do not want the next child. Factors associated with unwillingness to add the child is of age, education, place of residence, the ideal number of children and gender of children still living (p value <0.05). The value of the child to be a factor that is highly correlated with the unwillingness to add the child, the child sex composition into enabling factors, especially boys. The use of contraception is high (77.5%), especially injections and pills do not follow the high knowledge about the advantages and disadvantages of the method, so that method of contraception is more effective and efficient is still rarely used. Add to children's unwillingness significantly associated with the use of modern contraception (p value <0.05). Having analyzed together unwillingness to add a child, sociodemographic factors, values and attitudes towards child birth with the use of contraception increases the odds of modern contraceptive use from 1.5 to 1.7. Unwillingness to add the child has a significant relationship to the behavior of KB on young couples who already have two children. Keywords: unwillingness to add children, young couples, family planning behavior.